2012
DOI: 10.1160/th11-10-0717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of matrix metalloproteinases in atherosclerotic plaques

Abstract: SummaryIschaemic stroke and myocardial infarction often result from the sudden rupture of an atherosclerotic plaque. The subsequent arterial thrombosis occluding the vessel lumen has been widely indicated as the crucial acute event causing peripheral tissue ischaemia. A complex cross-talk between systemic and intraplaque inflammatory mediators has been shown to regulate maturation, remodeling and final rupture of an atherosclerotic plaque. Matrix metalloproteinases (MMPs) are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 77 publications
1
21
0
3
Order By: Relevance
“…The degradation of the extracellular matrix by matrix metalloproteinases (MMPs), which were reported to be secreted by SMCs (SMA high ) and inflammatory cells such as macrophages, T cells and ECs (SMA low ) [29], is thought to contribute to atherosclerotic plaque instability [30]. Therefore, to evaluate whether IL-37 affects atherosclerotic stability, we first measured the collagen content of atherosclerotic plaque sections in mice fed a HFD for 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of the extracellular matrix by matrix metalloproteinases (MMPs), which were reported to be secreted by SMCs (SMA high ) and inflammatory cells such as macrophages, T cells and ECs (SMA low ) [29], is thought to contribute to atherosclerotic plaque instability [30]. Therefore, to evaluate whether IL-37 affects atherosclerotic stability, we first measured the collagen content of atherosclerotic plaque sections in mice fed a HFD for 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, selective MMP-12 inhibitors are available and have been used safely in phase II clinical studies in pulmonary disease [58]. Even so, deeply seated MMP-12 positive macrophages might be difficult to inhibit; and therefore a surrogate marker of efficacy, perhaps based on molecular imaging [59], might be needed as a precursor to any outcome trial.…”
Section: Mmp-12 Promotes Invasion Of Mouse Macrophages In Vitro and Imentioning
confidence: 99%
“…Such selective targeting appears feasible even with existing chemistries [82]; and innovative approaches are continually emerging [83]. The final missing link is the development of surrogate endpoints, most likely based on non-invasive imaging [59], to bridge the gap between small-scale phase II and costly phase III trials. With continuing energy and enthusiasm all these goals can be achieved.…”
Section: Final Conclusionmentioning
confidence: 99%
“…Cathepsins and MMPs are highly expressed and localized in rupture-prone areas such as the fibrous cap, plaque shoulder and plaque rupture area. Therefore, cathepsins and MMP as macrophage-related molecules and primary imaging targets have been studied 3,[20][21][22][23][24] (Table 1, Fig. 1).…”
Section: Macrophage-related Targetsmentioning
confidence: 99%
“…13 In addition, 18 F-FDG detects highly increased metabolic activity associated with atherosclerosis since the metabolic activities of cells are increased in the immune response area. 27,28,32 On the other hand, cathepsin protease activity and matrix metalloproteinases activity have been the main targets applied in fluorescent imaging, where diverse imaging probes were developed and used in apoE-/-mice. 2,23 These adhesion molecule and extracellular matrix targets, which are parenchymal components of atherosclerosis, can increase the success of imaging and many studies have in fact shown their application in pre-clinical and clinical trials.…”
Section: Macrophage-related Targetsmentioning
confidence: 99%